AN ASSESSMENT OF THE TECHNICAL SKILLS OF STUDENTS IN THE ANAMBRA STATE: IMPLICATION FOR THE DEVELOPMENT ENTREPRENEURSHIP IN ANAMBRA STATE, NIGERIA - Emeka Elee, Gabriel (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Technical and Vocational Education and Training (TVET) is essential in developing highly skilled workers to satisfy the requirements of various industries. An empirical study is required to assess students' technical competency in TVET programs. This is necessary to successfully equip students with technical abilities that satisfy their current job needs and professional expectations. In fact, very little is known about the technical abilities of college students attending technical schools. The present study evaluated students' technical skills at government technical colleges in Anambra State, Nigeria. Two hundred fifty-five students were purposively pooled from the government technical college located in different parts of Anambra State and participated in the study. They completed a questionnaire measuring technical skills in six dimensions. The result revealed a high technical competence outcome for material and application (75.5%), work planning (71%), practical knowledge (66.7%), and theoretical knowledge (59.4%). Also, the findings indicated low technical skills for equipment maintenance (15.6%) and workshop management (18.1%). The result has implications for the sustainability and development of TVET in Nigeria.